Cold compression in direct recycling of aluminium 6061 - Chan, Boon Loong (2016)
In conventional recycling method, the aluminium scrap undergoes melting process whereby only 52% of the aluminium are recycled and the others are wasted in terms of melting loss, dross, extrusion scraps and etc. Other than material loss, the energy usage needed for conventional process are very high with energy consumption of 6000 kcal/kg and high operation costs due to the large number of operation. This research focus on one of the least researched direct recycling method that is by cold compression. Only one optimum chip size was used, that is (4-6) mm x (3.5-4.5) mm x (1.45-1.55) mm. The chips were cold compressed with a Force (F) of 35, 40 and 45 tons with variable in Holding Time (t = 1, 5 and 10 minutes). The compressed samples were then placed into the furnace to be sintered at different Temperature (T) namely, 0°C (no sintering), 500°C and 600°C. Both the mechanical properties (Ultimate Tensile Strength, UTS and Elongation to Failure, ETF) and the physical properties (Density, D and Micro-hardness, MH) were then tested. Response surface methodology (RSM) was then applied to identify the optimal variable parameters for specific goals. It was found that an increased in the compression force above the optimum condition will not bring any significant outcome on the compressed specimen. Whereas, sintering process increases the UTS to maximum of 14.67 MPa at sintering temperature of 600°C. But at the same time, the specimen that was sintered at 600°C show low ETF of only 1.23%. As for specimen that were not sintered (0°C), the lowest recorded UTS is 2.77 MPa but having better microhardness that was even higher if compared to the reference specimen with microhardness of 117.10 HV. Even though there is an improvement in mechanical and physical properties but the microstructure of the sample reveal that there is lack of bonding in the structure as the chips were more to overlapping each other rather than inter-locking one another. Further improvement in terms of shear deformation like hot extrusion is highly recommended to ensure better material bonding and powder metallurgy may be one of the other ways to strength the recycled chips as powdered aluminium sintered better than aluminium chips.